Ontario's educational assessment policy and practice: a double-edged sword?. Issue 6 (2nd November 2018) - Jang, Eunice Eunhee; Sinclair, Jeanne
Abstract: This paper examines assessment policies for K-12 education in Ontario, Canada. We begin with a discussion of Ontario's education system, and then turn our focus to Ontario's K-12 assessment policies serving multiple purposes for accountability and classroom learning. We first examine the Educational Quality and Accountability Office (EQAO), which is responsible for Ontario's province-wide literacy and numeracy assessments by focusing on the nature of its educational stakes, its implications for Ontario's diverse student populations and its alignment with Ontario's curriculum. We then turn to Ontario's policies geared towards classroom-based, teacher-led assessments, such as the Growing Success initiative and the Steps to English Proficiency assessment framework. Together, these policies coexist and function like a double-edged sword for teachers because of conflicting expectations and roles. We conclude with some suggestions for further enhancing Ontario's assessment policies through the integration of technology and building of teachers' assessment competencies.